DIVERSITY AND DISTRIBUTION OF MOLLUSCA AT VERAVAL COSTAL AREA, GUJARAT, INDIA - RACHNA N. RAVALIYA; JATIN V. RAVAL (The Bioscan, 2020)
Among the eight oceanic states of India, Gujarat, located on the western coast of India, with the shoreline of 1650 km. Diversity and distribution of marine molluscs were studied seasonally along the intertidal zone of Veraval. Veraval is situated at the coast of Saurashtra, Gujrat. The Mollusca fauna represented by 50 species belonging to 16 order and 25 families were collected and documented. Members of families like Cerithiidae, Muricidae and Turbinidae were reported throughout the study. Results showed that main molluscan populace belonged to class Gastropods, some of the maximum abundant species were Anachis terpsichora, Cantharus undosus, Turbo coronetus, Turbo intercostalis and Tibia curta, Cerithium sp., Murex sp., etc. Species mentioned above were observed throughout the study. The study of the distribution of marine molluscs was studied using the quadrat method. High species diversity was noted during winter and monsoon in the site studied. Dominated gastropod families Turbinidae, Buccinidae, Muricidae, Columbellidae, Carithiidae were observed during all the seasons. Carithiidae showed the highest density, abundance and frequency ranged from 5.06, 14.3, 66.66% while Buccinidae and Columbellidae showed the lowest density, abundance and frequency ranged from 0.03, 1.0, 3.3% during the study.